A Scale for Appraising the Leaf Blight of Wheat Caused by Alternaria Triticimaculans - Perelló, Analía Edith (1998)
The aim of this work was to present an scale of measurement for appraising the progress of leaf blight of wheat (Alternaria triticimaculans) in the field. Approximately three hundred diseased leaves of wheat at the milky ripe stage from an artificially inoculated crop, were collected. Based on leaf affected area in relation to the total leaf area, a nine grade scale was propose as a rapid technique to estimate this foliar disease.